SAT1 promotes the progression of OA by regulating TRIM33-mediated p53 acetylation to enhance ferroptosis - Jiexiang Yang; Jing Jiang; Jing Wang; Lin Luo (PLoS ONE, 2025)
Background Ferroptosis is a nonapoptotic form of cell death characterized by lipid peroxidation and intracellular iron accumulation. OA is a prevalent joint disease, and as OA progresses, inflammation or iron overload can induce ferroptosis in chondrocytes. However, research on genes that play important roles in this process remains insufficient. Methods In this study, we identified the ferroptosis-related gene SAT1 by analyzing OA-associated GEO datasets. For in vivo experiments, we induced an OA mouse model by transecting the medial meniscus ligament. In vitro, we analyzed the biological functions of SAT1 in ATDC5 cells using Cell Counting Kit-8 (CCK-8), trypan blue staining, Western blot, and detection of ferroptosis-related indicators. Additionally, we explored the mechanisms underlying SAT1’s role in OA progression through immunoblotting, ubiquitination, and acetylation immunoprecipitation experiments. Results Bioinformatics analysis revealed a close association between OA and ferroptosis. Our experimental results showed that overexpression of SAT1 effectively induced ferroptosis in ATDC5 cells. Mechanistically, SAT1 promoted p53 stability by downregulating TRIM33, which inhibits p53 acetylation. By suppressing TRIM33 expression, SAT1 enhanced p53 acetylation and stability, thereby increasing ferroptosis and exacerbating OA progression. Conclusion In summary, our data indicate that SAT1 is a potential key gene in OA, revealing the crucial role of the SAT1-TRIM33-p53 axis in OA pathogenesis. This axis promotes ferroptosis by enhancing p53 acetylation, suggesting that targeting SAT1 may represent a novel therapeutic strategy for improving OA.